Successful Development and Implementation of a Large Virtual Interprofessional Education Activity Applying the Social Determinants of Health - Karl R. Kodweis; Elizabeth A. Hall; Chelsea P. Renfro; Neena Thomas-Gosain; Robin Lennon-Dearing; Jonathon K. Walker; Tyler M. Kiles (MDPI AG, 2022)
Interprofessional education (IPE) activities provide students insight into healthcare teams, shared decision-making, and social determinants of health (SDOH). Virtual IPE activities with large student populations or across multicampus have not been evaluated. The study aimed to explore the interprofessional competency growth in students, across several disciplines, following participation in a large-scale, virtual IPE activity. Students from pharmacy, medicine, social work, and physician assistant programs across Tennessee participated in an IPE patient case and SDOH in fall 2020 and fall 2021. Pre- and postsurveys included Likert ranking of 16 statements based on the 2011 Interprofessional Education Collaborative (IPEC) framework. A total of 607 students completed surveys (overall response rate, 76%). Wilcoxon signed-rank tests were performed on the pre-/postsurvey data, in aggregate and by discipline. Significant increases in all IPEC competency statements were seen, both in aggregate (100% of statements with p < 0.001) and in pharmacy (100% of statements with p < 0.001) and medicine subgroups (94% of statements with p < 0.001). Implementing large virtual IPE activities involving a complex patient case and SDOH significantly increased student IPEC competency outcomes for participating students, whether in aggregate or on a discipline-specific basis.